Reading the Bible in an Age of Crisis : Political Exegesis for a New Day - Worthington, Bruce (Book collections on Project MUSE., 2015)
We live in an age in which economic, ecological, and political crises are not the exception, but the rule. The Cold War polarities that shaped an earlier "political exegesis" have been replaced; Bruce Worthington argues that increasingly, crisis is the engine of a global "turbo-capitalism." In this volume, edited by Worthington, biblical scholars and activists describe and exemplify the shape of a biblical interpretation that takes contemporary crisis seriously as its most important context. Succinct opening essays summarize the salient aspects of our critical situation, especially in relation to the dominance of capitalism and its pervasive values; in later parts, contributions address themes of economic, political, and environmental crisis in dialogue with texts from the First and Second Testaments. Throughout the volume, the authors are careful to describe the basis for making interpretive analogies across historical, cultural, and socioeconomic distances between the world of the Hebrew Bible, the New Testament, and our own. Richard A. Horsley writes a postscript pointing to next steps in political interpretation.